Inter-Professional Collaboration and Patient Mortality: Protocol for a Systematic Review and Meta-Analysis - Sandesh Pantha; Martin Jones; Richard Gray (MDPI AG, 2020)
Inter-professional collaboration is a process in which health professionals from different disciplines work together, sharing their ideas and opinions to plan evidence-based care. Nurses and doctors spend most of their time providing direct patient care. Therefore, effective interprofessional collaboration may be important in ensuring safe and effective patient care. There are no systematic reviews that have evaluated the association between nurse-doctor collaboration and patient outcomes in medical and surgical settings. We will conduct a systematic search of five key databases MEDLINE, EMBASE, PsycInfo, CINAHL, and the Cochrane register. We will include observational and experimental research that tests the association between levels of inter-professional collaboration and medical and surgical inpatient mortality. Two reviewers will independently conduct title and abstract, full-text screening, and data extraction. The Effective Public Health Practice (EPHPP) tool will be used to determine the quality of the included studies. If sufficient studies are available, we will undertake a meta-analysis. The protocol is registered with the international prospective register of systematic reviews (PROSPERO-CRD42019133543).